Flexible topological liquid diode catheter. (March 2020) - Li, J.; Zheng, H.; Zhou, X.; Zhang, C.; Liu, M.; Wang, Z.
Abstract: Spontaneous and directional transport of various liquids in open and closed spaces is of great importance in various energy, water, and medical applications. Despite extensive progress in engineering diverse open surfaces to rectify liquid transport, the implementation of the diode-like liquid transport in a closed system is still rare. In this study, we present the design of flexible liquid diode catheters internally decorated with asymmetric reentrant structure that allows for the efficient and unidirectional transport of diverse liquids. We also elucidate that the hydrodynamic transport behaviors in the closed diode catheters are primarily dominated by the interplay between the surface effect and the bulk effect, which are distinctly different from those on open liquid diodes. The flexible liquid diode catheters can preserve their directional transport behaviors even under mechanical bending or twisting and under various liquids from low-surface-tension liquids, medical solutions to lubricant oils. The combination of extraordinary flexibility, durability, and stability promises the development of liquid transport devices that can work in various configurations and applications. Graphical abstract: Image 1 Highlights: Developing a flexible liquid diode catheter for unidirectional liquid transport. Liquid behavior in the diode catheter is dominated by surface effect and bulk effect. The diode catheter can preserve its function under mechanical bending or twisting. The diode catheter can transport various liquids including medical solutions and oils.